PEMBERDAYAAN MASYARAKAT DALAM PENERAPAN HUKUM DAN KEARIFAN BUDAYA LOKAL PADA KEGIATAN USAHA PERTAMBANGAN DAN PERLINDUNGAN LINGKUNGAN HIDUP - Ilyas; Sri Rahayu; Sahra Roba; Sri Wahyuti (Ekasakti Jurnal Penelitian dan Pengabdian, 2024)
This research aims to examine community empowerment in the application of local laws and cultural wisdom in mining business activities and environmental protection in Batu Api Village, Batu Putih District, North Kolaka Regency. Research analysis method using qualitative techniques. As a result, local village communities do not have/are supported by optimal human resource competence in applying local laws and wisdom in mining business activities and environmental management. However, empowering the application of local laws and wisdom received great support from the local community. This empowerment is based on "Joint Commitment", and needs to be supported by Village Regulations (PERDES).